pH and temperature dual-sensitive liposome gel based on novel cleavable mPEG-Hz-CHEMS polymeric vaginal delivery system - Chen D (Dove Medical Press, 2012)
Daquan Chen,1,2 Kaoxiang Sun,1,2 Hongjie Mu,1 Mingtan Tang,3 Rongcai Liang,1,2 Aiping Wang,1,2 Shasha Zhou,1 Haijun Sun,1 Feng Zhao,1 Jianwen Yao,1 Wanhui Liu1,21School of Pharmacy, Yantai University, 2State Key Laboratory of Longacting and Targeting Drug Delivery Systems, Yantai, 3School of Pharmaceutical Sciences, Shandong University, Jinan, People's Republic of ChinaBackground: In this study, a pH and temperature dual-sensitive liposome gel based on a novel cleavable hydrazone-based pH-sensitive methoxy polyethylene glycol 2000-hydrazone-cholesteryl hemisuccinate (mPEG-Hz-CHEMS) polymer was used for vaginal administration.Methods: The pH-sensitive, cleavable mPEG-Hz-CHEMS was designed as a modified pH-sensitive liposome that would selectively degrade under locally acidic vaginal conditions. The novel pH-sensitive liposome was engineered to form a thermogel at body temperature and to degrade in an acidic environment.Results: A dual-sensitive liposome gel with a high encapsulation efficiency of arctigenin was formed and improved the solubility of arctigenin characterized by Fourier transform infrared spectroscopy and differential scanning calorimetry. The dual-sensitive liposome gel with a sol-gel transition at body temperature was degraded in a pH-dependent manner, and was stable for a long period of time at neutral and basic pH, but cleavable under acidic conditions (pH 5.0). Arctigenin encapsulated in a dual-sensitive liposome gel was more stable and less toxic than arctigenin loaded into pH-sensitive liposomes. In vitro drug release results indicated that dual-sensitive liposome gels showed constant release of arctigenin over 3 days, but showed sustained release of arctigenin in buffers at pH 7.4 and pH 9.0.Conclusion: This research has shed some light on a pH and temperature dual-sensitive liposome gel using a cleavable mPEG-Hz-CHEMS polymer for vaginal delivery.Keywords: mPEG-Hz-CHEMS polymer, pH-sensitive liposomes, thermosensitive, liposome gel, vaginal delivery